Benefit and harm of cryptocurrency as the official currency of a state - Trisna Taufik Darmawansyah; Miko Polindi; Putri Diesy Fitriani; Yani Aguspriyani; Rezky Mehta Setiadi; Sanawi Sanawi (Journal of Enterprise and Development (JED), 2023)
Purpose — The paper highlights two different opinions among scholars regarding the permissibility of cryptocurrency and explores the factors that contribute to these opinions. Additionally, the article discusses the potential risks associated with cryptocurrency, such as the lack of intrinsic value and the potential for use in illegal activities. Overall, the article seeks to provide insights into the Shariah perspective on cryptocurrency and its potential impact on the financial industry.Method — In conducting a SWOT (strengths, weaknesses, opportunities, and threats) analysis on cryptocurrency, the author gathered data from previous studies, literature in English, Indonesian, and Arabic. Then, the data collected through the SWOT analysis was analyzed using the principles of mashlahah and mafsadah and the principles of maqasid al-shariah. The appropriate method for analyzing data in this study is secondary data analysis.Result — Cryptocurrency is an innovation that has never happened before, especially in the financial world. Cryptocurrency brings many benefits but also brings losses, as evidenced by the weakness of the system and external activities. Based on the SWOT analysis, it appears that the losses or mafsadah tend to be more than the mashlahah, meaning that problems and conflicts will arise if cryptocurrency is used as the official currency of a country.Contribution — The paper makes an important academic contribution by using the Islamic concept of Maqashid al-Sharia, specifically the analysis of mashlahah (benefits) and mafsadah (harms), to evaluate the potential use of cryptocurrencies as national currencies.